Atomic Fe‐Doped MOF‐Derived Carbon Polyhedrons with High Active‐Center Density and Ultra‐High Performance toward PEM Fuel Cells. Issue 13 (14th February 2019) - Deng, Yijie; Chi, Bin; Li, Jing; Wang, Guanghua; Zheng, Long; Shi, Xiudong; Cui, Zhiming; Du, Li; Liao, Shijun; Zang, Ketao; Luo, Jun; Hu, Yongfeng; et al.
Abstract: A metalorganic gaseous doping approach for constructing nitrogen‐doped carbon polyhedron catalysts embedded with single Fe atoms is reported. The resulting catalysts are characterized using scanning transmission electron microscopy, X‐ray photoelectron spectroscopy, and X‐ray absorption spectroscopy; for the optimal sample, calculated densities of Fe–N x sites and active N sites reach 1.75812 × 10 13 and 1.93693 × 10 14 sites cm ‐2, respectively. Its oxygen reduction reaction half‐wave potential (0.864 V) is 50 mV higher than that of 20 wt% Pt/C catalyst in an alkaline medium and comparable to the latter (0.78 V vs 0.84 V) in an acidic medium, along with outstanding durability. More importantly, when used as a hydrogen–oxygen polymer electrolyte membrane fuel cell (PEMFC) cathode catalyst with a catalyst loading as low as 1 mg cm ‐2 (compared with a conventional loading of 4 mg cm ‐2 ), it exhibits a current density of 1100 mA cm ‐2 at 0.6 V and 637 mA cm ‐2 at 0.7 V, with a power density of 775 mW cm ‐2, or 0.775 kW g –1 of catalyst. In a hydrogen–air PEMFC, current density reaches 650 mA cm ‐2 at 0.6 V and 350 mA cm ‐2 at 0.7 V, and the maximum power density is 463 mW cm ‐2, which makes it a promising candidate for cathode catalyst toward high‐performance PEMFCs. Abstract : An atomic Fe‐doped MOF‐derived carbon polyhedron with high active‐center density and ultra‐high performance toward polymer electrolyte membrane fuel cells (PEMFC) is fabricated using a novel metallorganic gaseous doping strategy, which is a promising candidate for high‐performance practical PEMFC.